Pendampingan Penyusunan Manajemen Operasional Pembukuan dan Administrasi Kelompok Tani di Sembalun, Nusa Tenggara Barat - Widia Febriana; R. Ayu Ida Aryani; Melati Rosanensi; Muliani; Lina yunita (Insan Kreasi Media, 2022)
Bookkeeping and administration are needed as a forum for a group of people, including farmer groups. Bookkeeping is a recording process that is carried out obligatory and regularly in accumulating all types of data and information about finances consisting of liabilities, income, assets, costs and capital. The total value of the gift and income of goods or services, ends with the preparation of daily cash and a ledger in the form of a balance sheet, as well as a profit and loss statement for the period of the year as described in Law Number 28 of 2007 Article 28. Regarding the bookkeeping as described in the Act, it emphasizes on all entrepreneurs about the importance of bookkeeping. Because the bookkeeping in the company's internal is the main basis that becomes the foundation of the accounting system. In the recorded accounting system, the company's financial movements can be known in detail. Bookkeeping and administration, the main tasks and functions of the Tourism Manager in Sembalun NTB, are a form of community service. This assistance aims to train farmers so that the management of bookkeeping and administration operations is properly recapitulated. The method used in this service activity consists of five months of observation, socialization, and direct assistance. As a result of this community service, participants were able to understand how to book and administer tourism in Sembalun, West Nusa Tenggara.